User and staff experiences of a revised process for coordinating support with shared decision making in the comorbidity field of practice: a qualitative interview study - Amanda Jones (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study aims to explore user and staff experiences of a revised process for coordinated individual planning (CIP) that involves the user alongside staff from social services and healthcare and incorporates shared decision-making (SDM). Method Eight staff members and five users participated in individual semi-structured interviews. The collected data were analysed using reflexive thematic analysis. Results Users and staff experienced that the revised CIP process facilitates emotional security through predictability. This predictability is attributed to the predetermined structure in the CIP process and the user involvement enabled through preparations, as well as the mutual trust that arises from following through on expectations and commitments. Furthermore, the importance of partnerships was highlighted. This refers to the intention of respecting users as contributors, the joint understanding achieved between staff and users, and the continuity of care ensured through staff collaboration. Conclusion The findings show that incorporating SDM through the CIP process can enhance structure, user involvement, and a sense of emotional security through the process.